Perancangan Konsep Museum Virtual Universitas Kristen Maranatha - Natanael, I Nyoman; Suhanjoyo, Shirly Nathania; Wianto, Elizabeth (Program Studi Desain Interior Unikom, 2023)
Maranatha Christian University Museum was officially established on October 16, 2015, to coincide with the 50th Anniversary of Maranatha Christian University. The museum, named